Ultraviolet actinic flux in clear and cloudy atmospheres: Model calculations and aircraft-based measurements - Palancar, Gustavo Gerardo (2011)
Ultraviolet (UV) actinic fluxes measured with two Scanning Actinic Flux Spectroradiometers (SAFS) aboard the NASA DC-8 aircraft are compared with the Tropospheric Ultraviolet-Visible (TUV) model. The observations from 17 days in July-August 2004 (INTEX-NA field campaign) span a wide range of latitudes (28°N-53° N), longitudes (45° Wĝ€"140° W), altitudes (0.1ĝ€"11.9 km), ozone columns (285-353 DU), and solar zenith angles (2°85°). Both cloudy and cloud-free conditions were encountered. For cloud-free conditions, the ratio of observed to clear-sky-model actinic flux (integrated from 298 to 422 nm) was 1.01±0.04, i.e. in good agreement with observations. The agreement improved to 1.00±0.03 for the down-welling component under clear sky conditions. In the presence of clouds and depending on their position relative to the aircraft, the up-welling component was frequently enhanced (by as much as a factor of 8 relative to cloud-free values) while the down-welling component showed both reductions and enhancements of up to a few tens of percent. Including all conditions, the ratio of the observed actinic flux to the cloud-free model value was 1.1±0.3 for the total, or separately 1.0±0.2 for the down-welling and 1.5±0.8 for the up-welling components. The correlations between up-welling and down-welling deviations are well reproduced with sensitivity studies using the TUV model, and are understood qualitatively with a simple conceptual model. This analysis of actinic flux observations illustrates opportunities for future evaluations of photolysis rates in three-dimensional chemistry-transport models.